Correction: Exploring the impact of total quality management initiatives on construction industry projects in Pakistan. - Nimra Afzal; Aamer Hanif; Muhammad Rafique (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274827.].